2018
DOI: 10.1188/18.onf.545-552
|View full text |Cite
|
Sign up to set email alerts
|

Use of Virtual Reality to Distract From Pain and Anxiety

Abstract: Virtual reality goggles may be a feasible, noninvasive alternative to traditional pharmacologic treatment. The cost of any intervention would need to be considered. Virtual reality should be researched and adapted to benefit patients in appropriate settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 25 publications
1
88
0
4
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1. Of the 6 studies, 1 was a randomized controlled trial, 17 1 was a case-controlled trial, 13 and the others were mainly a pre-post-test study design with a single arm. 11,12,18,19 In terms of study settings, only 2 studies were conducted at outpatient cancer care centers, while the others were conducted in hospital inpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. Of the 6 studies, 1 was a randomized controlled trial, 17 1 was a case-controlled trial, 13 and the others were mainly a pre-post-test study design with a single arm. 11,12,18,19 In terms of study settings, only 2 studies were conducted at outpatient cancer care centers, while the others were conducted in hospital inpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…Current research has demonstrated the application of VR in numerous medical settings. Outpatient settings where researchers have applied VR include periodontal scaling and root planing procedures (N = 50) in a dental hygiene clinic [12], bone marrow aspiration and biopsy procedure (N = 97) in an outpatient cancer center [15], serious hand injury requiring surgical wound care (N =98) in an outpatient surgical center [16] and cystoscopy in ambulatory surgical center (N = 45) [17].…”
Section: Uses Of Vrmentioning
confidence: 99%
“…Similar to the non-opioid approaches, VR is a non-pharmacological intervention that can benefit patients' pain with minimal side effects (Spiegel et al, 2019;Chan, Foster, Sambell, & Leong, 2018;Vazquez, Lara, Miller, Wiederhold, & Wiederhold, 2019;Glennon et al, 2018;Mohammad & Ahmad, 2018, Scapin, Echevarria-Guanilo, Junior, Goncalves, Rocha, & Coimbra, 2018. The use of technology to distract the patient from their pain complements traditional pain management methods.…”
Section: Virtual Realitymentioning
confidence: 99%
“…The use of technology to distract the patient from their pain complements traditional pain management methods. VR is a superior tactic compared to other mediums, such as television (Speigel et al, 2019) or music (Glennon et al, 2018). The technology can treat acute pain intraoperatively or during medical procedures, but long-term carryover effects have not been proven (Mallari et al, 2019).…”
Section: Virtual Realitymentioning
confidence: 99%
See 1 more Smart Citation